Exploring the boundaries of life cycle analysis in environmental hazard assessment - Diana Khripko; Samuel W. Short; Silviu O. Petrovan; David C. Aldridge; Julie Bremner; Andre M. Gomes; David F. Willer (Journal of Cleaner Production, 2025)

Flow Dynamics and Local Scour Around Seabed-Mounted Artificial Reefs: A Case Study from Torbay, UK - Amir Bordbar; Jakub Knir; Vasilios Kelefouras; Samuel John Stephen Hickling; Harrison Short; Yeaw Chu Lee (Journal of Marine Science and Engineering, 2025)
This study investigates the flow dynamics and local scour around a Reef Cube® artificial reef deployed in Torbay, UK, using computational fluid dynamics. The flow is modelled using Reynolds-Averaged Navier–Stokes (RANS) equations with a k-ω SST turbulence model. A novel hydro-morphodynamic model employing the generalized internal boundary method in HELYX (OpenFOAM-based) is used to simulate scour development. Model performance was validated against experimental data for flow fields, bed shear stress, and local scour. Flow simulations across various scenarios demonstrated that parameters such as the orientation angle and arrangement of Reef Cubes significantly influence flow patterns, bed shear stress, and habitat suitability. The hydro-morphodynamic model was used to simulate scouring around a reef cube in the Torbay marine environment. Results indicate that typical tidal flow velocity flow in the region is barely sufficient to initiate sediment motion, whereas extreme flow events, represented by doubling the mean flow velocity, significantly accelerate scour development, producing holes up to ten times deeper. These findings underscore the importance of considering extreme flow conditions in scour analyses due to their potential impact on the stability and failure risk of AR projects.

Mapping hazards to the global food system - David F. Willer; Samuel Short; Diana Khripko; Silviu O. Petrovan; Alec P. Christie; Julie Bremner; William J. Sutherland; David C. Aldridge (Environmental Monitoring and Assessment, 2024)
Environmental hazards associated with the global food system threaten societal integrity. Yet, there is a major data gap in the global understanding of how the prevalence of hazards is changing over time, how different classes of hazard are distributed, and whether the combined literature represents hazard prevalence equitably across research, policy and legislation, and news. Here, we explore this data gap, leveraging global research, policy, and news databases. We reveal increasing attention on food system hazards over time, in line with major geopolitical events. Coverage on environmental hazards is not distributed equally geographically, and media attention does not match research and policy evidence focus. Climate change and water scarcity in particular receive substantial attention across all source types, whilst, for example biodiversity loss, genetic erosion, or harmful algal blooms receive much less. Environmental, financial and food systems sustainability damage due to hazard neglect should be avoided and a first step is to understand, map, and quantify biases in focus.

From Refining Sugar to Growing Tomatoes - Samuel W. Short; Nancy M.P. Bocken; Claire Y. Barlow; Marian R. Chertow (Journal of Industrial Ecology, 2014)
Summary This article seeks to advance the understanding of the relationship between industrial ecology (IE) and business model innovation for sustainability as a means and driver of new value creation and competitive advantage by expanding the understanding of industrial symbiosis (IS) and internal symbiosis. This is explored through the case study of British Sugar, which, at the time of writing, is the UK's largest sugar producer by market share. Over the past three decades, the company has systematically sought opportunities to turn waste streams and emissions from their core production processes into useful and positive inputs to new product lines. Their core business is still sugar, but the business model has evolved to offer a broad range of additional synergistic and profitable product lines, including animal feed, electricity, tomatoes, and bioethanol. The research explores the temporal dimension of dynamic business model innovation, framing it in the context of a continuous evolutionary process rather than a discrete design activity. The case will be of interest as an additional contribution to the growing literature on IS; in offering an approach for linking the themes of IE literature and sustainable business model innovation more concretely in research and practice; and, by presenting the case as an evolutionary innovation process, the article furthers the emerging literature on business model innovation for sustainability.

Chronic Nutrient Enrichment Increases the Density and Biomass of the Mudsnail, Nassarius obsoletus - David Samuel Johnson; Meghan I. Short (Estuaries and Coasts, 2013)